The state of scientific research on the use of specialist knowledge in smuggling investigations (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The article substantiates that smuggling as a socially dangerous phenomenon has existed since the inception of the first state formations. Its emergence was facilitated by the desire to avoid paying customs duties and moving goods beyond the control of state authorities. It is established that in order to counteract smuggling, appropriate legal measures were introduced in different historical periods. It is emphasised that today the criminal offences related to smuggling include smuggling of cultural property, poisonous, potent, explosive substances, radioactive materials, weapons or ammunition (except for smooth-bore hunting weapons or ammunition), parts of rifled firearms, and special technical means of covertly obtaining information; smuggling of timber and valuable tree species; smuggling of goods (except for excisable goods and electricity); smuggling of excisable goods; smuggling of narcotic drugs, psychotropic substances, their analogues or precursors or counterfeit medicines.It is determined that in the modern period of development of the legal framework for combating crime and the scientific basis of such activities, which began in the early 2000s, attention has been repeatedly paid to the issues of ensuring effective investigation of criminal offences related to smuggling. It is established that some of the studies conducted still do not comply with the current doctrines of criminal law and criminal procedure, and some contain only descriptive recommendations on the typical types of forensic examinations conducted during the investigation. It is stated that the current level of forensic support for the use of special knowledge, technical and forensic support for the investigation of criminal offences related to smuggling is insufficient, and scientific research within the scope of this subject needs to be intensified.
Keywords: pre-trial investigation; criminal offence; scientific development; scientific support; smuggling; customs control.